High Temperature Composites From Renewable Resources: A Perspective on Current Technological Challenges for the Manufacturing of Non-Oil Based High Char Yield Matrices and Carbon Fibers - Natali, Maurizio; Rallini, Marco; Torre, Luigi; Puglia, Debora (Frontiers in Materials, 2022)
During last decades a plethora of high temperature materials have been developed to work as a Thermal Protection System (TPS). Carbon based materials such as graphite, which possesses low density, high heat capacity and high energy of vaporization, have been used as TPS material. However, graphite has relatively poor mechanical properties, but exhibits low resistance to the thermal shocks. Accordingly, to bypass the limitation of graphite, carbon ﬁbers are typically introduced in a carbon matrix to produce Carbon/Carbon Composites (CCCs). Among the different families of TPS solutions, Polymeric Ablative Materials (PAMs), produced combining high char yield matrices - mainly phenolic resins - and Carbon Fibers (CFs) are used to manufacture Carbon/Phenolic Composites (CPCs) i.e. the most important class of fiber reinforced PAM. Carbon fibers are traditionally produced from Polyacrylonitrile (PAN), Rayon and Pitch. Some limited researches also aimed to use cyanate-esters, bismaleimides, benzoxazines matrices in combination with ex-PAN-CFs, ex-Rayon-CFs, and ex-Pitch-CFs. In our paper, after covering the science and technology of these state-of-the-art fiber reinforced TPS materials, a review of current challenges behind the manufacturing of new, high char yield matrices and carbon fibers derived from alternative precursors will be provided to the reader. In particular, the possibility to produce CFs from precursors different from PAN, Rayon and Pitch will be reported and similarly, the technology of non-oil based phenolics, bismaleimides, cyanate-esters and benzoxazines will be discussed. The effect of the use of nanosized fillers on these matrices will also be reported. More in detail, after a preliminary section in which the state of the art of technologies behind carbon/phenolic composites will be covered, a second part of this review paper will be focused on the most recent development related to non-oil based phenolics and biomass derived carbon fibers. Finally, an outlook focused on the maturity of the lab-scale protocols behind the researches at the base of these non-traditional raw materials from an industrial point of view will conclude this review paper.